Violência doméstica e familiar contra a mulher: uma análise dos laudos periciais realizados no IML-RR - Pereira, Marcela Campelo (2013)
Violence must be interpreted, in addition to its ethical, moral, cultural and legal issue and as a public health problem. It is a worldwide phenomenon that hurts ethical principles of equality. Its effects are harmful to women's health, causing harm to their physical and mental health in addition to causing consequences for the family and the community. Despite all the rights gained, new laws existing Public Policy implemented, women continue to suffer violence. The objective of this research is to characterize the physical domestic violence and family, occurred in adult women, their socio-demographic and relationship to the perpetrator. For this, we outlined a documentary research, a descriptive and exploratory, in 2011, the Legal Medical Institute of Roraima (IML-RR), with analysis of reports of adult women both suffered domestic violence, referred for forensic examination and autopsy, the police stations in every state. Of the 1,111 cases of violence against women and unnatural death found, 811 (73%) reports contained information (a) offender (a). Of these reports, 616 (76%) were committed by offenders with ties of kinship, intimate partners or family arrangements. The domestic violence affects all walks of society, especially women who declared the home (32.6%) and single (59.1%). The vast majority (68.5%) was provided by the Women's Police Stations (DDM) from the capital, Boa Vista. The body parts were atigidas head and neck, described in 388 reports (63.4%), caused by hard-hitting action in 543 cases (88.7%). In 468 (76%) cases were committed by offenders who maintain or maintained affectionate relations with the victim, among these, 271 (44%) were declared as husband / partner, boyfriend or partner. We can conclude that, in our sample, we found a high prevalence of domestic violence (76%), especially by intimate partners.